2002
DOI: 10.1212/wnl.58.9.1348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiepileptic drugs on bone density in ambulatory patients

Abstract: Epilepsy and its therapy, including the newer drugs, are risk factors for low bone density, irrespective of vitamin D levels. Skeletal monitoring with the institution of appropriate therapy is indicated in patients on chronic antiepileptic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
191
4
25

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 323 publications
(226 citation statements)
references
References 33 publications
6
191
4
25
Order By: Relevance
“…According to WHO criteria, 63, 5% of the patients had a diagnosis of osteopenia / osteoporosis in at least one of the sites measured. This incidence is higher than uncontrolled studies reported in the literature 6,11,12 . Because of the cross-sectional nature of the present study, it was not possible to know if the bone loss is specifically related to the use of AEDs or if there are other reasons for the differences appreciated in this study.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…According to WHO criteria, 63, 5% of the patients had a diagnosis of osteopenia / osteoporosis in at least one of the sites measured. This incidence is higher than uncontrolled studies reported in the literature 6,11,12 . Because of the cross-sectional nature of the present study, it was not possible to know if the bone loss is specifically related to the use of AEDs or if there are other reasons for the differences appreciated in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…We have demonstrated significant abnormalities of bone metabolism, characterized by reduced BMD, reduced 25OHD, and increased AP. Previous studies have related these findings to chronic use of AEDs 5,6,11,12 . Serum levels of calcium and PTH were normal and similar to the control group.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations